Give us a game: Evaluating the opportunities that exist for English footballers to play in the English Premier League - Bullough, S.; Mills, A. (International Journal of Sports Science and Coaching, 2014)
The purpose of this study was to provide a detailed, large-scale retrospective analysis of the number of English footballers that have been developed to play in the English Premier League (EPL) over twenty seasons. Unlike previous research, we examined appearance data as opposed to percentage of squad data enabling a more accurate representation of English players appearing in the EPL. The findings revealed a steady decline in the number and proportion of appearances made by English players in the EPL throughout the twenty season period. However, the results also indicated that the rate of decline had abated since the inception of UEFA's home-grown rule. The results support the view that opportunities for indigenous players have diminished since the EPL's inception. Given the short-term, results-focused culture that prevails in the EPL, this would appear to present a major challenge for governing bodies, particularly those working in elite player development. Discussion surrounding how these challenges might be met is presented.